Hexagrid-Voronoi transition in structural patterns for tall buildings - Elena Mele; Massimiliano Fraldi; Gian Maria Montuori; Gianpaolo Perrella; Vincenzo Della Vista (Fracture and Structural Integrity)
In this paper, a first insight into the role that non-conventional structural patterns might play in the design of tall buildings is presented. The idea is to explore the mechanical properties of selected non-conventional structural patterns, in the form of both regular (Hexagrid) and irregular (Voronoi tessellation inspired) arrays, in order to assess their actual applicability in tall building design. For this aim, the concept of Representative Volume Element (RVE) and a classical homogenization-based micromechanical approach are employed for identifying the pattern units and deriving the relevant generalized stress-strain relationships. In the case of irregular patterns based on Voronoi diagrams, obtained by perturbing prescribed key geometrical features of hexagrids, a statistically significant sample of RVEs is defined on the basis of sensitivity analyses, and the related mechanical characterization is developed in statistical terms. Finally, a preliminary stiffness-based design procedure is proposed and applied to a tall building model with Voronoi exoskeleton. In conclusion, a discussion on the effectiveness of the design procedure and on the structural efficiency of the Voronoi patterns for tall buildings is presented